PENGARUH LATIHAN SMALL SIDED GAMES DAN LATIHAN RONDO TERHADAP KETEPATAN PASSING PADA PEMAIN KLUB FUTSAL ALDIFA BANJARMASIN - Fitrian, Zanzabil Adwa (Universitas Negeri Surabaya, 2022)
This study was conducted to determine the effect of the Small Sided Games (SSG) and Rondo exercises on the accuracy of passing on the players of the Futsal club Aldifa Banjarmasin. The experimental method used in this research is the